Hospital compound-level endoscopy training quality performance: scoping the spectrum - Eley, Catherine; Brown, Chris; Hawkes, Neil D.; Egan, Richard J.; Lewis, Wyn G. (Endoscopy International Open, 2022)
Background and study aims This study aimed to assess the quality of endoscopy training in a UK Statutory Educational Body compared with Joint Advisory Group on Gastrointestinal Endoscopy Training standards (JETS).Methods A total of 28,298 training procedures recorded by 211 consecutive cross-specialty trainee endoscopists registered with JETS in 18 hospitals during 2019 were analyzed. Data included trainer and trainee numbers, training list frequency, procedures, direct observation of procedural skills (DOPS) completion, and key performance indicators.Results Annual median training procedures per hospital were 1395 (interquartile range (IQR) 465–2365). Median trainers and trainees per unit were 11 (6–18) and 12 (7–16), respectively, (ratio 0.8 [0.7–1.3]). Annual training list frequency per trainee was 13 (10–17), 35.0 % short of Joint Advisory Group (JAG) standard (n = 20, P = 0.001, effect size –0.56). Median points per adjusted training list were 11 (5–18). Median DOPS per trainee and trainer were three (1–6) and four (1–7) respectively; completing 0.2 DOPS (0.1–0.4) per list and amounting to six (2–12) per 200 procedures: fewer than half of the JAG standard (20 per 200) (P < 0.001, –0.61). Esophagogastroduodenoscopy median KPI: J maneuver 94 % (90–96), D2 intubation 93 % (91–96); Colonoscopy KPI: cecal intubation 82 % (72–90), polyp detection rate 25 % (18–34). Compound hospital score ranged from nine to 26 (median 17 [14–20]).Conclusions Important performance disparity emerged with three-fold variation in compound hospital training quality and most units underperforming compared with JAG standards. Trainees and training program directors should be aware of such metrics to improve quality endoscopy educational programs and consider formal adjuncts to optimize training.